DIGITAL MARKETING STRATEGIES ON INSTAGRAM ADS: A CASE STUDY OF CLONY OFFICIAL - Saputra, Rafly Yunanda; Nurchaerani, Meiyanti (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study investigated the digital marketing strategies employed by Clony Official, a new venture specializing in ETU tote bags, through Instagram advertising. Using a qualitative approach, in-depth interviews with the business owner explore the effectiveness of various Instagram ad formats, content creation strategies, audience targeting methods, and measurement of ad performance. Findings reveal insights into types of ads utilized, challenges faced, such as budget constraints and ad fatigue, and opportunities identified, including enhanced targeting and influencer collaborations. Conclusions offer recommendations for optimizing digital marketing efforts on Instagram, emphasizing budget allocation, content diversification, influencer partnerships, and interactive features. This research contributes valuable insights into enhancing online presence and sales through effective social media advertising.